Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1108/ijis-05-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Factors and maturity level of entrepreneurial universities in Spain

Abstract: Purpose The entrepreneurial university is being widely studied, given its importance as an agent in economic and social development. This paper presents the findings of a study that had a twofold objective. First, it sought to establish a model of maturity for the measurement of the level of academic entrepreneurship in universities. Second, it aimed to apply this maturity model to a sufficiently wide and varied sample of faculties to discover their current level of academic entrepreneurship, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
11
0
4
Order By: Relevance
“…In order to meet the research objectives, a questionnaire was used that had been previously designed and validated by Errasti et al [27] to measure the maturity of academic entrepreneurship among different faculties. This questionnaire, based on the original instrument by Markuerkiaga et al [38], consisted of 14 blocks of mostly closed questions, with the inclusion of a smaller number of open questions to allow participants to provide evidence and/or add comments and clarifications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to meet the research objectives, a questionnaire was used that had been previously designed and validated by Errasti et al [27] to measure the maturity of academic entrepreneurship among different faculties. This questionnaire, based on the original instrument by Markuerkiaga et al [38], consisted of 14 blocks of mostly closed questions, with the inclusion of a smaller number of open questions to allow participants to provide evidence and/or add comments and clarifications.…”
Section: Methodsmentioning
confidence: 99%
“…Since the studies published to date are not focused on models that encompass all the factors covered in the literature, there is a need to further the knowledge of the determinant factors of the entrepreneurial university, and the extent of their influence. To this end, Errasti et al [27] devised and validated a model of maturity for the measurement of the level of academic entrepreneurship among faculties and universities. The model included thirteen factors: Legal and administrative context; business and organisational context; entrepreneurship funding; training in entrepreneurship for faculty staff; inclusion of professionals from businesses and organisations in the development and delivery of the curriculum; mission and strategy; policies and procedures; support from the management team; organisational design; training and research in entrepreneurship; extra-curricular training; active methodologies; and internationalisation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the research on the quality evaluation system of innovation and entrepreneurship in universities in China, we found that research on the effectiveness of innovation and entrepreneurship education and the attainment of goals are more and more, and fewer studies are needed to evaluate and improve the quality of innovation and entrepreneurship education. The weight of indicators determines the tendency is more prominent, the logic and relevance between the indicators are poor, and the objectivity and rationality of the evaluation results are difficult to guarantee [3][4][5][6]. Therefore, as one of the important links in innovation and entrepreneurship education in universities, the research on the evaluation system of innovation and entrepreneurship education quality is particularly urgent.…”
Section: Introductionmentioning
confidence: 99%